Tax-based Own Resources as a Core Element of a Future-Oriented Design of the EU System of Own Resources - Margit Schratzenstaller (Intereconomics, 2018)
Sustainability-oriented tax-based own resources would do more than just help to close the existing sustainability gaps in EU taxation. Member States primarily consider their individual net positions, i.e. the difference between their payments into the EU budget and the transfers they receive out of it, when determining the benefits derived from the EU (budget). Much less attention is paid to indirect benefits from EU membership and expenditures, which generally exceed Member States' contributions to the EU budget considerably.
Keywords: 330